Nuclear actin assembly is an integral part of decidualization in human endometrial stromal cells - Isao Tamura; Kei Miyamoto; Chiharu Hatanaka; Amon Shiroshita; Taishi Fujimura; Yuichiro Shirafuta; Yumiko Mihara; Ryo Maekawa; Toshiaki Taketani; Shun Sato; Kazuya Matsumoto; Hiroshi Tamura; et al. (Communications Biology, 2024)
Abstract Decidualization of the human endometrium is critical for establishing pregnancy and is entailed by differentiation of endometrial stromal cells (ESCs) into decidual cells. During decidualization, the actin cytoskeleton is dynamically reorganized for the ESCs’ morphological and functional changes. Although actin dynamically alters its polymerized state upon external stimuli not only in the cytoplasm, but also in the nucleus, nuclear actin dynamics during decidualization have not been elucidated. Here, we show that nuclear actin was specifically assembled during decidualization of human ESCs. This decidualization-specific formation of nuclear actin filaments was disassembled following the withdrawal of the decidualization stimulus, suggesting its reversible process. Mechanistically, RNA-seq analyses revealed that the forced disassembly of nuclear actin resulted in the suppression of decidualization, accompanied with the abnormal upregulation of cell proliferation genes, leading to incomplete cell cycle arrest. CCAAT/enhancer-binding protein beta (C/EBPβ), an important regulator for decidualization, was responsible for downregulation of the nuclear actin exporter, thus accelerating nuclear actin accumulation and its assembly for decidualization. Taken together, we demonstrate that decidualization-specific nuclear actin assembly induces cell cycle arrest for establishing the decidualized state of ESCs. We propose that not only the cytoplasmic actin, but also nuclear actin dynamics profoundly affect decidualization process in humans for ensuring pregnancy.